Análisis de pérdidas poscosecha de maíz (Zea Mays) en el cantón Pindal provincia de Loja - Puente Torres, Luis Ángel (2015)
The present work of investigation Analysis of losses pos-harvests of maize (Zea Mays) in the canton Pindal Loja's province, it had as object: 1) the operations Evaluate pos-crop and commercialization of maize, 2) To construct an offer of managing pos-harvests and alternative commercialization for the maize adapted to the zone of study and 3) To socialize results obtained with producers and interested in general. The used methodology was based on the summary of secondary information, registered in books and Internet sites; as well as of primary information obtained across surveys, to the producers of the zone. The study added to it in laboratory of the losses he pos-harvests across a random sampling in: crop of maize, storage, transport and commercialization; with base in it an offer was generated to reduce the losses in the most critical phase. Finally the results were socialized in participative form by the farmers. The results established the phases with major losses, which are in the crop and storage, where it silvered alternatives of mitigation in the following aspects: for the crop, to reduce the assault of rodents; for which it is suitable to practice the burning of controlled form, achieving the major possible quantity destroying hereby the existing burrows; thinking that it is the best alternative that allows to control partly the assault of this plague in field conditions; on the other hand, to avoid the assault of insects and fungi in massive form, it is necessary to realize the crop in all that the grain has reached his physiological maturity and a degree of dampness reaches 13 to 15 %. In the storage the utilization of metallic silos, as well as also sacks of polypropylene, will give a good staunchness on having guarded the product, without leaving of side the technical procedure of conservation of the product along the whole stored one.